Immunohistochemistry, histopathology and infrared spectral histopathology of colon cancer tissue sections. Issue 1 (7th December 2012) - Kallenbach‐Thieltges, Angela; Großerüschkamp, Frederik; Mosig, Axel; Diem, Max; Tannapfel, Andrea; Gerwert, Klaus
Abstract During the past years, many studies have shown that infrared spectral histopathology (SHP) can distinguish different tissue types and disease types independently of morphological criteria. In this manuscript, we report a comparison of immunohistochemical (IHC), histopathological and spectral histopathological results for colon cancer tissue sections. A supervised algorithm, based on the "random forest" methodology, was trained using classical histopathology, and used to automatically identify colon tissue types, and areas of colon adenocarcinoma. The SHP images subsequently were compared to IHC‐based images. This comparison revealed excellent agreement between the methods, and demonstrated that label‐free SHP detects compositional changes in tissue that are the basis of the sensitivity of IHC. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)